Depression and pain dynamics in lumbar degenerative disk disease: a systematic review and meta-analysis - Karibayeva, Indira; Kuanyshbekov, Yerzhan; Idayat, Malika; Turdaliyeva, Botagoz; Makhanbetkhan, Shayakhmet (Acta Biomedica Atenei Parmensis, 2024)
Background and aim: This study systematically reviews the literature on changes in depression and pain scores in patients with lumbar degenerative disc disease (LDDD) after treatment initiation. Methods: A comprehensive review of PubMed, Web of Science, Science Direct, Academic Search Complete, and Google Scholar was performed. Pooled prevalence estimates, subgroup analysis, sensitivity analysis, and publication bias assessments were performed. Results: We identified eight eligible studies with 634 LDDD patients. Our meta-analysis indicated a slight reduction in the mean Beck Depression Inventory scores from baseline (11.51) to three months post-treatment (9.18). Conversely, there was a significant decrease in the mean Visual Analogue Scale back pain scores from baseline (6.72) to three months post-treatment (2.62). This suggests that treatment for LDDD may reduce pain levels in the short term; however, its effect on depression is limited. Additionally, patients in the conservative treatment group exhibited higher rates of depression both at baseline (12.32) and at the 3-month follow-up (9.45) than those in the operative treatment group (11.23 at baseline and 8.57 at the 3-month follow-up). In terms of pain, patients in the conservative treatment group reported lower pain scores at baseline (6.14) but higher scores at the 3-month follow-up (3.53) than those in the operative treatment group (7.68 at baseline and 1.45 at the 3-month follow-up). Conclusions: Our findings underscore the need for integrated treatment approaches that address both depression and pain to improve the outcomes of patients with LDDD. Although pain reduction is achievable, the management of depression remains a challenge.